COVID-19 Mortality in a Pediatric Patient with Hemoglobin SC Disease and Alpha-Thalassemia Trait - Joshua E. Motelow; Stacie Kahn; Patrick T. Wilson (Case Reports in Critical Care)
As the pandemic continues to evolve, more cases of COVID-19 in pediatric patients are being detected. A 12-year-old boy with HbSC disease alpha-thalassemia trait presented to a pediatric emergency room with fever and weakness. His vital signs were notable for fever, tachypnea, and tachycardia. His physical exam was concerning for increased work of breathing. He tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by PCR although his hemoglobin level remained near his baseline. His chest radiograph showed a retrocardiac opacity concerning for evolving acute chest syndrome. He decompensated quickly requiring invasive mechanical ventilation and exchange transfusion. He received hydroxychloroquine, broad-spectrum antibiotics, and enoxaparin for DVT prophylaxis. Despite showing clinical signs of improvement, he became acutely hypoxemic and suffered a cardiac arrest. We believe this to be an unusual case of a pediatric patient with HbSC disease and COVID-19. We outline clearly the course of illness and treatments trialed, which can prove beneficial to providers facing similar challenges as this virus continues to strike areas around the world. Although children have significantly better outcomes than adults, providers must remain vigilant while treating any patient with a hemoglobinopathy in the setting of severe COVID-19.